ANALISIS PENDAPATAN MASYARAKAT PENGRAJIN ANYAMAN ROTAN DI DESA BENUIS KECAMATAN SELIMBAU KABUPATEN KAPUAS HULU - Kurniawan, M Agus; Fahrizal, M; AM, Iskandar (Universitas Tanjungpura, 2016)
Rattan is a non-wood forest product that is potential to develop as a commodity of trade, both for domestic consumption and for export. Rattan is widely used as material for woven craft by the people in Benuis Village, Selimbau Subdistrict, Kapuas Hulu Regency. This study aims to find out about the average income of woven rattan craftsmen in Benuis Village, Selimbau Subdistrict, Kapuas Hulu Regency, the factors that affect the craftsmen’s total revenue, and the efforts made to improve the craftsmen’s income. This research is quantitative descriptive with survey method and interview technique with a guide questinnaire. The samples werw selected through purposive sampling with 57 (fifty seven) respondents spread across three hamlets in Benuis Village. The results of data analysis showed that the craftmen’s average income from selling woven rattan is IDR 1,173,421.05/household/year, plus additional from non rattan products of IDR 6,917,544/husehold/year and 8,090,965/household/year. After deducting the average cost of IDR 120,070,00, te average net income is IDR 7,970,895/household/year. The regression analysis obtained from three independent variabels obtained the value of Fcount = 0.9871.594 < TTabel (α=0,05;57) = 2.40, so H0 is accepted and Ha is rejected. It means that the number of working days and additional income other than from rattan handicraft Bussines simultaneously had no significant effect on the total income of craftsmen. Keyword: Benuis village, communit, income, woven rattan craftsmen